UZBEKISTAN AND THE UNITED STATES OF AMERICA UNDER CRIMINAL LAW CRIMINAL RESPONSIBILITY ISSUES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article compares the specifics of criminal liability for arms trafficking at the federal level of the United States and the criminal law (precedent documents) of New York and Texas with the norms of liability for such crimes in the Criminal Code of the Republic of Uzbekistan. scientifically analyzed and suggestions for improving national legislation.